Spaces of Refusal: Silence, Solitude, and Existential Feminist Agency in Desai’s Fire on the Mountain - Sharma, Khum Prasad; Sharma, Manisha Kumari (Mindscape: A Journal of English & Cultural Studies, 2024)
This paper examines Anita Desai’s Fire on the Mountain as a feminist–existentialist narrative in which silence, solitude, and withdrawal function as modes of resistance rather than signs of passivity. Drawing on Simone de Beauvoir’s existential feminism, Judith Butler’s theory of gender performativity, and Hélène Cixous’s concept of écriture féminine, the study analyzes the lives of three women-Nanda Kaul, Raka, and Ila Das-to demonstrate how female subjectivity is forged through refusal, non-engagement, and ethical choice. Employing a qualitative textual methodology and close reading, the study argues that Desai reconfigures silence as an active strategy of agency that challenges patriarchal expectations surrounding aging, femininity, and social participation. The findings reveal that the narrative resists normative feminist paradigms of empowerment by foregrounding inward, existential modes of freedom. The study contributes to South Asian feminist literary studies by repositioning Desai’s novella within contemporary debates on gender, agency, and existential autonomy.